Penanggulangan Dampak Negatif Media Sosial Melalui Peran Guru dan Masyarakat di Sekolah - Muhammad Yasin; Siti Sri Fattul Jannah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The growing flow of globalization makes all countries and levels of society able to accept the entry and exit of outside influences on various aspects of life. The flow of globalization followed by technological developments can have a considerable impact on society, especially for teenagers who can affect their lifestyle and will have various positive and negatif impacts on these changes. This study aims to describe the role of teachers both at school and in the community in overcoming the negatif impact of social media related to juvenile delinquency at Sepaso Junior High School, Bengalon and what efforts have been made by the school and community leaders to tackle juvenile delinquency. This research method uses a qualitative method with a descriptive approach. This study utilizes data collection techniques in terms of interviews, document analysis, observation, documentation, and drawing structured conclusions as a support for the completeness of analysis and research so that it requires skills for researchers in terms of recording and collecting research data. The results of this study can be concluded that the role of teachers and the community in guiding a teenager is important so that teenagers are no longer wrong in terms of using social media as a means of broad information. The implication of the school is to hold regular socialization with students or parents of SMP Sepaso Bengalon students in order to find out the negatif impact of social media and how to use social media correctly and the information that is searched on social media can be according to the age of the students as well as an educator always guides and directs his students to always do positive activities. Meanwhile, the implication of the community is that community leaders always create a positive environment for teenagers with a minimal environment for crime and parents provide a positive environment in their homes and work together between schools and community leaders in guiding or supervising the activities of the students. teenagers to stay away from activities that are included in the juvenile delinquency section.